Jargon on Instagram Features - Gaby, Fendianus; Putu Desi Anggerina Hikmaharyanti (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
Jargon is a special vocabulary used in certain area of life (environment). Jargon is rarely understood by people because it is very specific in order. The purpose of this study was to identify the form and meaning of jargons in Instagram features. The data of this study were taken from the form of words inInstagram social media platform. This study considered to use the theory of Halingga (2004) on forming jargon and Leech (1981) on meaning. Descriptive qualitative method was applied to analyze the collected data. This study found 12 data (60%) for word forms, 3 data (15%) for the phrase form, 5 data (25%) for the abbreviated form and 12 data (60%) for acronym. The meaning of the jargons reached more denotatively the same as their real meaning characteristics. Jargon is a special vocabulary used in certain area of life (environment). Jargon is rarely understood by people because it is very specific in order. The purpose of this study was to identify the form and meaning of jargons in Instagram features. The data of this study were taken from the form of words inInstagram social media platform. This study considered to use the theory of Halingga (2004) on forming jargon and Leech (1981) on meaning. Descriptive qualitative method was applied to analyze the collected data. This study found 12 data (60%) for word forms, 3 data (15%) for the phrase form, 5 data (25%) for the abbreviated form and 12 data (60%) for acronym. The meaning of the jargons reached more denotatively the same as their real meaning characteristics.